Management’s perception towards factors that affecting Oil Extration Rate (OER) of FGV plantations under Wilayah Serting / Mohammad Jazli Jamaluddin - Jamaluddin, Mohammad Jazli (Faculty of Plantation and Agrotechnology, 2017)
Oil palm gives the most high yield compare to all oil crops in the world. Oil extraction rate from palm oil bunches become so valuable to generate a good economy to our country. There are several factors that have potential to affects oil extraction rate of oil palms such as harvesting, ripeness, loose fruits and transportation. Therefore, the research was conducted to study of the factors that affecting oil extraction rate (OER) in oil palm plantations which has been conducted at FGV plantations under Wilayah Serting. A survey was conducted to 80 samples out of 100 populations in achieving the objectives. The data analyses were used reliability test, ANOVA, regression and correlation was analysed by using SPSS 20. The result obtained from this study was all the factors have a significant different since p-value 0.001 is less than 0.05. Through regression analysis found that the most factors contributed to the OER was ripeness of the bunch.